Quantification of Chemokine CCL5 in Patients with Diabetes Mellitus Type 2 and/or Chronic Periodontitis: Preliminary Study - Sansores-España DDS, Luis (2017)
The purpose of the present study was to quantify the presence of chemokine CCL5 (RANTES) in gingival crevicular fluid (LCG) in patients with chronic periodontitis (PC) and / or type 2 diabetes mellitus (DM2). A comparative cross-sectional study was conducted in 40 patients. LCG was taken from periodontal pockets and gingival grooves from 4 patient groups (10 per study group); patients who received periodontal, antibiotic and anti-inflammatory treatment 6 months prior to the study or who had systemic disease other than DM2 were excluded. Concentrations of CCL5 were determined by LUMINEX® assays. Descriptive statistics, one-way ANOVA, Student's T, and Pearson's correlation were performed. The quantification of CCL5 was higher in the patients who presented both diseases, followed by the group with only PC, healthy and the group with only DM2. No significant difference was found between groups and there was no correlation between quantifications and glycemic indicators. Although the differences were not significant, the group of patients with both diseases had the highest CCL5 quantification. The expression of CCL5 in LGC should be considered as a potential inducer of periodontal destruction, its determination could be useful for monitoring the health/disease of periodontal tissues.